Humanização no atendimento odontológico: abordagem curricular nos Cursos de Odontologia do Estado de São Paulo - Souza, Hideki Shirosaki Marçal de [UNESP] (2015)
The pedagogical project based on community demands let the formation of a professional who understands welcoming and bonding actions addition to technical skills. Humanization at dental care is highly important due to uneven relation between scientific / technical advances in dentistry and the quality of human contact. The dental treatment goes beyond the field of scientific knowledge. Therefore, the dental treatment requires balance among technical skill, scientific training, and humanist vision of health promotion. Contemporarily, humanization is understood as tripod based on user's rights, dental practice and organization of a humanized model. Curriculum integration of ethical, humanistic, scientific and technical contents is an important and current challenge on teaching / learning process for professionals at Dentistry. This paper aims to know the teaching of welcoming and bonding actions at Dental Schools of São Paulo State, Brazil. The results show that São Paulo State, Brazil, has 39 institutions and 61 Dentistry Courses. 47.55% teaches welcoming and bonding actions. 9.83% offers this matter with the teaching option. 21.31% do not teach. 21.31% do not present data for analysis It is suggested that dentists reflect on the urgent need on theoretical basis of humanization and patient-professional relationship for health care